-4+(-5)+6=m

Simple and best practice solution for -4+(-5)+6=m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+(-5)+6=m equation:


Simplifying
-4 + (-5) + 6 = m
-4 + -5 + 6 = m

Combine like terms: -4 + -5 = -9
-9 + 6 = m

Combine like terms: -9 + 6 = -3
-3 = m

Solving
-3 = m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
-3 + -1m = m + -1m

Combine like terms: m + -1m = 0
-3 + -1m = 0

Add '3' to each side of the equation.
-3 + 3 + -1m = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -1m = 0 + 3
-1m = 0 + 3

Combine like terms: 0 + 3 = 3
-1m = 3

Divide each side by '-1'.
m = -3

Simplifying
m = -3

See similar equations:

| 6e^3x=84 | | .4(x-5)=.2(10-12x)+x | | 20z(2/z-1/5z) | | 3y=10+10x | | 7x-13=190 | | 9v=24+6v | | 6+5(-4)=t | | S=48+(-2s) | | 6y+2(y-2)=5(y+1)-2 | | (x*x)+(4x)-32=0 | | 3(8bx+y)=23bx-4y | | 25a=81*100 | | -2+x+10=4x+23 | | f=-52+52 | | 25a=9*100 | | 9t-7=-7+4t | | g-7=12 | | 13x/3=1521 | | 33+y=4 | | Cos^-1(14/25) | | .5x+(.25*50)=26.5 | | v=3.14r^220 | | 8v-5=7w-9 | | 7x-8(3+2x)=4x+11 | | 1/3h=9 | | 21x-21=6y+6 | | (2x+5)-49(3.14)x^2=0 | | S+(s*2)=48 | | 8B*AB=-4AB | | 9y-12=20+y | | g^2-19g+9=0 | | 8[x+2]=6 |

Equations solver categories